1977
DOI: 10.1080/14640747708400614
|View full text |Cite
|
Sign up to set email alerts
|

How Children Learn to Draw Realistic Pictures

Abstract: Children of ages 5 to 17 years were given a real scene to draw from a fixed viewpoint. Their drawings were classified according to the type of drawing system used, and given a score for the number of correct representations of occlusion by overlap. Six classes of drawing system used were identified, and it was found that with increasing age children were able to use an increasingly complex type of system. This development appeared to take place in discrete stages and covered the whole age range tested. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 1 publication
0
45
0
1
Order By: Relevance
“…However, studies such as Willats (1977aWillats ( , 1977b, Duthie (1985) and Cox (1986) indicated that some individuals do not adopt a system of drawing in perspective even when they have reached the age when it is deveiopmentally possible. Linear perspective is rarely used before adolescence, and even then only infrequently (Golomb 1992).…”
Section: Basic Research On Drawingmentioning
confidence: 99%
See 4 more Smart Citations
“…However, studies such as Willats (1977aWillats ( , 1977b, Duthie (1985) and Cox (1986) indicated that some individuals do not adopt a system of drawing in perspective even when they have reached the age when it is deveiopmentally possible. Linear perspective is rarely used before adolescence, and even then only infrequently (Golomb 1992).…”
Section: Basic Research On Drawingmentioning
confidence: 99%
“…Kindler (1992) has pointed out the necessity of careful consideration of learning strategies which children spontaneously employ to solve problems of pictorial representation-Strategies such as occlusion and temporal order to name two. Projection systems have been looked at by Willats (1977a), Cox (1986) and Chen (1984), but there is a lack of information about other strategies.…”
Section: Basic Research On Drawingmentioning
confidence: 99%
See 3 more Smart Citations